Stem Cell-Derived Exosome in Cardiovascular Diseases: Macro Roles of Micro Particles - Yuan, Ye; Du, Weijie; Liu, Jiaqi; Ma, Wenya; Zhang, Lai; Du, Zhimin; Cai, Benzhi (Frontiers in Pharmacology, 2018)
The stem cell-based therapy has emerged as the promising therapeutic strategies for cardiovascular diseases (CVDs). Recently, increasing evidence suggest stem cell-derived active exosomes are important communicators among cells in the heart via delivering specific substances to the adjacent/distant target cells. These exosomes and their contents such as certain proteins, miRNAs and lncRNAs exhibit huge beneficial effects on preventing heart damage and promoting cardiac repair. More importantly, stem cell-derived exosomes are more effective and safer than stem cell transplantation. Therefore, administration of stem cell-derived exosomes will expectantly be an alternative stem cell-based therapy for the treatment of CVDs. Furthermore, modification of stem cell-derived exosomes or artificial synthesis of exosomes will be the new therapeutic tools for CVDs in the future. In addition, stem cell-derived exosomes also have been implicated in the diagnosis and prognosis of CVDs. In this review, we summarize the current advances of stem cell-derived exosome-based treatment and prognosis for CVDs, including their potential benefits, underlying mechanisms and limitations, which will provide novel insights of exosomes as a new tool in clinical therapeutic translation in the future.